2004
DOI: 10.1152/ajpendo.00274.2003
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates interleukin-6 and tumor necrosis factor-α gene expression in human subcutaneous adipose tissue

Abstract: High circulating levels of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) are found in patients with hyperinsulinemia. Insulin stimulates release of IL-6 from adipocyte cultures, and it stimulates IL-6 gene expression in insulin-resistant, but not control, rat skeletal muscle. In addition, TNF-α may be involved in the pathogenesis of insulin resistance. Therefore, we studied the effect of insulin on IL-6 and TNF-α gene expression in human skeletal muscle and adipose tissue. Nine healthy young volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 35 publications
6
103
3
1
Order By: Relevance
“…Esposito et al (2002) showed that intravenous glucose administration increases concentrations of the pro-inflammatory markers IL-6 and IL-18 and hypothesize that low-fibre diets can thus contribute to hyperglycaemia with resultant increases in the mentioned cytokines . As insulin is known to stimulate IL-6 secretion (Krogh-Madsen et al, 2004), it can be predicted that diets that induce a relatively low post-prandial insulin response will be associated with below-average serum concentrations of IL-6 and CRP. Therefore, it may be possible to moderate CRP concentrations by avoiding high-insulinresponse starchy foods (high-glycaemic index foods) and emphasizing whole-grain foods rich in amylose and fibre (Jenkins et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esposito et al (2002) showed that intravenous glucose administration increases concentrations of the pro-inflammatory markers IL-6 and IL-18 and hypothesize that low-fibre diets can thus contribute to hyperglycaemia with resultant increases in the mentioned cytokines . As insulin is known to stimulate IL-6 secretion (Krogh-Madsen et al, 2004), it can be predicted that diets that induce a relatively low post-prandial insulin response will be associated with below-average serum concentrations of IL-6 and CRP. Therefore, it may be possible to moderate CRP concentrations by avoiding high-insulinresponse starchy foods (high-glycaemic index foods) and emphasizing whole-grain foods rich in amylose and fibre (Jenkins et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble fibre is fermented by anaerobic bacteria in the colon to short-chain fatty acids (Cummings and Englyst, 1987) including acetate, which inhibits serum FFA release from adipocytes (Scheppach et al, 1988;Ferchaud-Roucher et al, 2005), resulting in an increased insulin sensitivity (Trowell, 1975). It is possible that the resultant lower insulin levels can reduce the amount of IL-6 produced as shown in vitro (Vicennati et al, 2002) and in vivo (Krogh-Madsen et al, 2004) and thus subsequently CRP. Furthermore, adiponectin may lower circulating FFA concentrations by increasing fatty acid oxidation by skeletal muscle (Yamauchi et al, 2001) and by increasing hepatic FFA extraction directly (Tschritter et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding acute regulation of 'insulin-resistance' genes, insulin has been found to increase IL6 expression in vitro in human adipocytes [25] and in 3T3-L1 cells [26], and transiently in a study in vivo in human adipose tissue [27]. Data on TNF expression are inconsistent, with one study reporting a transient increase in TNF mRNA by insulin in vivo with no change in serum TNF [27], while another in vivo study [28] and one in vitro study using human adipose tissue [29] found no effect of insulin on TNF expression.…”
Section: Introductionmentioning
confidence: 99%
“…Data on TNF expression are inconsistent, with one study reporting a transient increase in TNF mRNA by insulin in vivo with no change in serum TNF [27], while another in vivo study [28] and one in vitro study using human adipose tissue [29] found no effect of insulin on TNF expression. Insulin has been reported to decrease HSD11B1 expression in vitro [13], and not to change expression during a 3-h insulin infusion in human adipose tissue [28].…”
Section: Introductionmentioning
confidence: 99%
“…The two mentioned methodologies are principally different as several organs (liver [13], pancreas [14], muscles [15], endothelium [16] and adipose tissue [17]) as well as regulatory mechanisms (hypothalamicpituitary-adrenal axis [18]) influences the concentration of glucose and/or insulin in the human body, but not in isolated blood samples. Glucose and/or insulin concentration changes in aliquots during incubation might therefore be different from glucose and/or insulin homeostasis in vivo.…”
Section: Introductionmentioning
confidence: 99%